2017
DOI: 10.1155/2017/9505460
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Role of Human Cationic Trypsinogen (PRSS1) p.R122H Mutation in Hereditary and Nonhereditary Chronic Pancreatitis: A Systematic Review and Meta-Analysis

Abstract: Background Environmental factors and genetic mutations have been increasingly recognized as risk factors for chronic pancreatitis (CP). The PRSS1 p.R122H mutation was the first discovered to affect hereditary CP, with 80% penetrance. We performed here a systematic review and meta-analysis to evaluate the associations of PRSS1 p.R122H mutation with CP of diverse etiology. Methods The PubMed, EMBASE, and MEDLINE database were reviewed. The pooled odds ratio (OR) with 95% confidence intervals was used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Variable rates of PRSS1 gene mutations have been reported in chronic pancreatitis patients of idiopathic etiology (0-21%). 14,[25][26][27][28] Similar to the current findings, several studies internationally have reported that PRSS1 mutations were rare or absent in patients with chronic pancreatitis, [28][29][30][31][32][33] although others reported PRSS1 mutations at frequencies of 1.5-33% amongst alcohol-related pancreatitis patients. 27,34 SPINK1 mutations are found in 1-3% of the general population, 24 and idiopathic chronic pancreatitis is strongly associated with the common SPINK1 high-risk genotype N34S.…”
Section: Discussionsupporting
confidence: 84%
“…Variable rates of PRSS1 gene mutations have been reported in chronic pancreatitis patients of idiopathic etiology (0-21%). 14,[25][26][27][28] Similar to the current findings, several studies internationally have reported that PRSS1 mutations were rare or absent in patients with chronic pancreatitis, [28][29][30][31][32][33] although others reported PRSS1 mutations at frequencies of 1.5-33% amongst alcohol-related pancreatitis patients. 27,34 SPINK1 mutations are found in 1-3% of the general population, 24 and idiopathic chronic pancreatitis is strongly associated with the common SPINK1 high-risk genotype N34S.…”
Section: Discussionsupporting
confidence: 84%
“…It was also suggested that autoimmune pancreatitis may be related to PRSS1 variants [12]. However, a recent large metaanalysis has shown that one of the most frequent PRSS1 variant, p.R112H, was strongly associated with an increased risk of hereditary CP but not with sporadic CP, either alcoholic or idiopathic [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to [33] and [34], the gene encoding the serine protease enzyme group is the PRSS1 gene. This gene encodes trypsinogen, a member of the serine protease trypsin family.…”
Section: In-silico Analysis Of Trypsin Of Various Speciesmentioning
confidence: 99%